How Can Man Become Virtuous from The Confucian Perspective - Nasyanti, Pratiwi (Published by Confucius Institute UNS, 2024)
Human values have always been a fundamental element in supporting a harmonious life in society. Humanistic philosophy, as taught by Confucius, stresses moral virtues and an ethical way of life that promotes. Though there are many things in the world that are in contradiction with human values, despite advancements in science and technology cannot ensure that human virtue values remain the primary focus over profits. After all, prioritizing one's own interests over the welfare of society will inevitably cause significant harm and social disintegration. For thousands of years, Confucian thought has been considered capable of shaping the balance of life, justice, filial piety, and ethical behavior in accordance with Confucius' rules to maintain social harmony in China, including when confronted with the country's social-economic problems. Then, from a Confucian standpoint, how can man become virtuous, and what lessons can we learn? Another question is, what, according to this philosophy, distinguishes humans? Confucius laid great emphasis on moral education to cultivate an individual as a person. His moral education aimed to improve character and behavior, training people to become completely virtuous and 君子 (jūnzǐ). According to Confucius, a man will be able to become virtuous by cultivating the teachings of virtue along with his own self-development, and the environment is a significant influence on a person's behavior. Both now and in the next decades, a leader who is conscious of virtue values and is concerned with the subject's well-being and national unity, in addition to self-development and self-cultivation efforts in carrying out the five virtues, is also highly needed.